OPTIMIZING INSIDE THERMAL INSULATION OF WALLS IN TROPICAL HOUSES BASED ON THE COOLING LOAD AND LIFE CYCLE COST ANALYSIS (LCC) - Muhammad, Fadhil
Air conditioning (AC) in buildings in the tropical area consumes a lot of energy. More than 50% of the building's total operational electric power is for AC. The cooling load influences energy consumption in the room. This research discusses potential energy efficiency strategies by reducing cooling load using inside thermal insulation. This study aims to determine the optimum type and thickness of inside thermal insulation for its operational costs. There are three types of insulation, namely Polyurethane, Styrofoam, and air gap with multiplex coverage. The effects of the three insulation are simulated in various thicknesses from 0.5 to 8 cm. This insulation's effectiveness is affected on a brick wall of a bedroom in a residential building in Bandung, using the Energyplus software. Comparative analysis was carried out to see the effect of the type and thickness of inside thermal insulation on the costs during building operations with an intermittent and 24-hour AC system. The results show that the best inside thermal insulation with 8cm Polyurethane material reduces AC energy consumption by 75%. The inside thermal insulation thickness analysis showed that the optimum thickness for Polyurethane, Styrofoam, and air gap materials are 3-4cm, 4cm, and 4cm thickness, respectively. Life Cycle Cost (LCC) analysis is carried out to calculate investment and operational costs for various insulation systems. The results showed that Polyurethane insulation's investment cost was the greatest, followed by Styrofoam and air gap, but Polyurethane showed the most significant cooling load reduction. Inside thermal insulation with Polyurethane is recommended in rooms with high intensity and duration of AC. It is recommended for rooms with a moderate or low cooling requirement to use inside thermal insulation with Styrofoam or air gap. Inside thermal insulation using air gap has the most economical investment cost. The adequate inside thermal insulation thickness is up to 4 cm thickness. More than 4cm of insulation layer will reduce the effective space area, which is not proportional to the decrease in the cooling load and the building energy consumption. Inside thermal insulation in thin sheets is highly recommended for buildings in tropical areas that use AC.